Polyphosphate accelerates factor V activation by factor XIa - Choi, Sharon H.; Smith, Stephanie A.; Morrissey, James H. (Thrombosis and Haemostasis, 2015)
Factor Va enhances the rate of prothrombin activation by factor Xa by four to five orders of magnitude. Production of initiating levels of factor Va from its precursor, factor V, is a critical event early in haemostasis, as factor V exhibits negligible cofactor activity. While thrombin is the most potent physiological back-activator of factor V, the first prothrombinase complexes require a source of factor Va prior to thrombin generation. A recent study by Whelihan et al. (J Thromb Haemost 2010; 8:1532–1539) identified factor XIa as a candidate for the initial thrombin-independent activation of factor V, although this reaction was slow and required relatively high concentrations of factors V and XIa. Activated platelets secrete polyphosphate, which we previously showed to be potently procoagulant. We now report that polyphosphate greatly accelerates factor V activation by factor XIa, and that this is supported by polyphosphate polymers of the size secreted by activated human platelets. This finding provides additional evidence that factor XIa-mediated generation of factor Va may contribute to the initiation of haemostasis.
Keywords: Polyphosphate; factor V; factor XI; prothrombinase